Fluid Mechanical Stress and the Platelet - Goldsmith, Harry L; Yu, Simmon S. K; Marlow, Jean (Thrombosis and Haemostasis, 1975)
Platelet thrombi in suspensions stirred in an aggregometer or subjected to shear flow in a Couette viscometer or circular tube can only form as a result of collisions between the cells. In whole blood, the presence of the red cells results in pronounced lateral displacements of the paths of the platelets through the vessel, which in turn increases the frequency of collisions between platelets and also makes possible platelet-wall interactions. In addition, blood cells in a suspension undergoing shear flow are subjected to fluid stresses which can result in their deformation. Such stresses may locally attain high values in the arterial circulation at bifurcations, sharp bends and stenoses where the flow is disturbed. Since platelet thrombi have been found downstream of sites of such geometry, the effects of high and variable shear stress on the platelet release reaction and aggregation were investigated. Washed platelets containing C14-serotonin in Tyrodes-albumin solution were subjected to oscillatory flow at 37° C and provided the time average wall velocity gradient was above 2,000 sec-1, the thrombin-induced release of serotonin was appreciably greater than in the corresponding controls incubated at rest. No measurable serotonin was released as a result of flow alone. This synergistic effect of oscillatory shear flow was also noted in the presence of inhibitors of the release reaction.